Teachers’ Strategies in Developing Scientific Literacy for Children with Special Needs in Inclusive Early Childhood Education - Teti Ratnawulan; Aznan Che Ahmad; Zulfa Rahmah Effendi; Rifqi Zaeni Achmad Syam; Willya achmad (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The phenomenon of low scientific literacy among early childhood learners, particularly in inclusive educational institutions, indicates a gap between policy and classroom practice. Children with special needs often experience limited access to adaptive science learning, even though scientific literacy skills are essential for developing reasoning and problem-solving abilities in daily life. This study aims to analyze teachers’ strategies for developing scientific literacy among children with special needs in inclusive early childhood education and to identify the challenges and solutions implemented by teachers at Ibnu Sina Islamic Kindergarten in Bandung Regency. The study employed a qualitative case study design, using in-depth interviews, participatory observations, and analysis of learning documents. Data were analyzed using Miles and Huberman’s interactive model, with validity ensured through triangulation and member checking. The findings reveal that teachers applied differentiated instruction, interpersonal communication, and the use of visual media, simple technology, and the surrounding environment as a natural laboratory. Collaboration among classroom teachers, special education teachers, parents, and the principal emerged as a key factor for success. The main challenges included limited resources, pedagogical competence, and the lack of specialized training in scientific literacy for children with special needs. The implications of this study emphasize the importance of enhancing teacher training, strengthening systemic support, and fostering school–family partnerships to achieve sustainable, inclusive science education.